A generic method for PLC control system design based on Digital Twin - Hao Shi; Qingliang Zhu; Jingde Bo; Jiayang Shi; Tao Zhao (PLoS ONE, 2025)
This study explores a design method for electrical control systems based on the Digital Twin (DT) from the perspective of control engineers. The proposed method enables engineers to systematically develop and validate such systems, thereby enhancing the quality and efficacy of industrial digitalization. By identifying critical challenges in DT-based control system design, we proposed a maturity evaluation framework to ensure that the DT’s fidelity aligns with the requirements of control system design application scenarios. Subsequently, a comparative analysis of virtual and physical commissioning was conducted, leading to the formulation of a structured implementation framework for DT-based control system design. A six-floor elevator DT was employed as the controlled object to demonstrate the proposed method. A virtual commissioning platform was constructed to validate the feasibility and reliability of the control system. This approach provides actionable insights for the corresponding physical entity to optimize construction schemes, commissioning workflows, and operation adjustments. The practical results demonstrate that the proposed DT-based design method of the electrical control system enables high-fidelity validation of production line design, reduces resource consumption during physical equipment commissioning, and significantly enhances development efficiency and quality while shortening construction and commissioning timelines.